Housing Instability Results in Increased Acute Care Utilization in an Urban HIV Clinic Cohort. (27th March 2019) - Clemenzi-Allen, Angelo; Neuhaus, John; Geng, Elvin; Sachdev, Darpun; Buchbinder, Susan; Havlir, Diane; Gandhi, Monica; Christopoulos, Katerina
Abstract: Background: People living with HIV (PLWH) who experience homelessness and unstable housing (HUH) often have fragmented health care. Research that incorporates granular assessments of housing status and primary care visit adherence to understand patterns of acute care utilization can help pinpoint areas for intervention. Methods: We collected self-reported living situation, categorized as stable (rent/own, hotel/single room occupancy), unstable (treatment/transitional program, staying with friends), or homeless (homeless shelter, outdoors/in vehicle) at an urban safety-net HIV clinic between February and August 2017 and abstracted demographic and clinical information from the medical record. Regression models evaluated the association of housing status on the frequency of acute care visits—urgent care (UC) visits, emergency department (ED) visits, and hospitalizations—and whether suboptimal primary care visit adherence (<75%) interacted with housing status on acute care visits. Results: Among 1198 patients, 25% experienced HUH. In adjusted models, unstable housing resulted in a statistically significant increase in the incidence rate ratio for UC visits (incidence rate ratio [IRR], 1.35; 95% confidence interval [CI], 1.10 to 1.66; P < .001), ED visits (IRR, 2.12; 95% CI, 1.44 to 3.13; P < .001), and hospitalizations (IRR, 1.75; 95% CI, 1.10 to 2.77; P = 0.018). Homelessness led to even greater increases in UC visits (IRR, 1.75; 95% CI, 1.29 to 2.39; P < .001), ED visits (IRR, 4.18; 95% CI, 2.77 to 6.30; P < .001), and hospitalizations (IRR, 3.18; 95% CI, 2.03 to 4.97; P < .001). Suboptimal visit adherence differentially impacted UC and ED visits by housing status, suggesting interaction. Conclusions: Increased acute care visit frequency among HUH-PLWH suggests that interventions at these visits may create opportunities to improve care.